PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN SMART APPS CREATOR (SAC) 3 PADA MATERI PECAHAN SENILAI DI KELAS IV SEKOLAH DASAR - Tiara Utari; Syafri Ahmad; Masniladevi; Risda Amini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted because the utilization of mathematics learning media in elementary schools was not optimal. The purpose of this study is to develop valid and practical learning media on fractions worth in grade IV elementary school. The study used a research and development (R&D) approach with the ADDIE model. The stages in the research process using the ADDIE model consist of analysis, design, development, implementation, and evaluation. Data were collected from the results of the validation questionnaire of material, linguistic, media experts, and based on a questionnaire of practicality responses from teachers and students. In this research, the trial school was class IV SDN 04 Bakir with 16 students. The research school was conducted in class IV SDN 03 Malepang with 13 students. The results of the Smart Apps Creator 3 learning media validity test in material aspects reached a percentage of 98%, the results of the language validity test amounted to 97% and the results of media validity reached 95.17%, all three of which were classified as very valid. The results of the practicality test in the trial school showed a teacher questionnaire percentage of 93.18% and a student questionnaire of 93.75%, both of which were in the very practical category. In addition, the results of the practicality evaluation in the research school received a score of 95.45% in the “very practical” category for the teacher questionnaire and 96.42% in the “very practical” category for the student questionnaire. Thus, it can be concluded that learning media using Smart Apps Creator 3 on fraction material in grade IV SD is valid and practical.